Pseudoprogression of thoracic tumor after radiotherapy in the era of immunotherapy: a case series - Xiang, Yongbo; Tang, Wei; Wang, Jianyang; Wang, Zhijie; Bi, Nan (Frontiers in Oncology, 2023)
Pseudoprogression is rarely mentioned after radiotherapy except for central nervous system tumors. With the widespread of immunotherapy, the incidence of pseudoprogression of thoracic tumor after radiotherapy is increasing. This study summarized the clinical features of pseudoprogression in 4 patients who had underwent thoracic radiotherapy after and/or followed by immunotherapy. All of them had received chemotherapy and immunotherapy before thoracic radiotherapy. After radiotherapy, pseudoprogression occurred within 3 months after initiation of immune consolidation/rechallenge therapy. At least a 20% increase in the sum of the longest diameter of target lesions were measured on their chest image. During this period, patients' ECOG PS scores remained stable, specific serum tumor markers did not increase significantly. Treatment strategies did not change after pseudoprogression. The causes of radiographic pseudoprogression in this case series may be attributed to disturbances such as pneumonitis, atelectasis, mucus blockages and infection. In the era of immunotherapy, pseudoprogression of thoracic tumors after chest radiotherapy might become a common phenomenon. It is important for us to identify pseudoprogression based on patient's general status, radiological changes, and laboratory tests.